La bande chantée : tradition orale et croyances pédagogiques dans le Corriere dei Piccoli - Lorenzo Di Paola; Eva Van de Wiele (Comicalités)
Corriere dei Piccoli emerged during a unique moment in Italian history characterized by the convergence of popular culture and new industrial and cultural practices that foreshadowed the future advent of mass media (Colombo, 1999). This article aims to investigate the processes of remediation that involves the communicative format of this renowned periodical, connecting it to a long tradition of oral and performative practices. Corriere dei Piccoli, in fact, effectively remediated (Bolter & Grusin, 2003) the ancient oral tradition of the “Cantastorie” (traveling entertainers who tell or sing stories in public squares with the aid of painted posters depicting key scenes from the tales), whose performances had a significant impact on the formal and meaning structures of the magazine. This process entails a collision between ancient narrative traditions and a novel media landscape characterized by the intersection of liberty, futurism, theatrical performances, and literary tradition. In this context, Corriere dei Piccoli stands as one of the privileged sites from which to observe the challenging process of modernization in Italy (Brancato, 2008).Additionally, the investigation will consider the educational practices related to orality and performance. Our main thesis posits that the magazine strikes a balance between traditional pedagogy and multimedia/multimodal entertainment. The rhymed captions used in the comics reflect the attention devoted to young readers’ literacy and emphasize the responsibility placed on parents and older siblings to “chaperone” their reading (as indicated by Sutliff Sanders, 2013). Following the same educational path, in its early years of publication, the magazine invested in a correspondence section where the mediating figure of Paola Lombroso actively promoted reading and writing through a dialogue with the readership. However, the remarkable Corrierino comic format not only educated children but also proposed a more consumerist lifestyle, which, on the one hand, tended to commodify children and, on the other hand (from a media education perspective ante litteram), provided useful tools to understand and navigate the media landscape of the time.